Comparative Catalytic Properties of Supported and Encapsulated Gold Nanoparticles in Homocoupling Reactions - Jang, Wongi; Yun, Jaehan; Ludwig, Luke; Jang, Su Guan; Bae, Jae Young; Byun, Hongsik; Kim, Jun-Hyun (Frontiers in Chemistry, 2020)
This report describes strategies to increase the reactive surfaces of integrated gold nanoparticles (AuNPs) by employing two different types of host materials that do not possess strong electrostatic and/or covalent interactive forces. These composite particles are then utilized as highly reactive and recyclable quasi-homogeneous catalysts in a C-C bond forming reaction. The use of mesoporous TiO2 and poly(N-isopropylacrylamide), PNIPAM, particles allows for the formation of relatively small and large guest AuNPs and provides the greatly improved stability of the resulting composite particles. As these AuNPs are physically incorporated into the mesoporous TiO2 (i.e., supported AuNPs) and PNIPAM particles (i.e., encapsulated AuNPs), their surfaces are maximized to serve as highly reactive catalytic sites. Given their increased physicochemical properties (e.g., stability, dispersity, and surface areas), these composite particles exhibit notably high catalytic activity, selectivity, and recyclability in the homocoupling of phenylboronic acid in water and EtOH. Although the small supported AuNPs display slightly faster reaction rates than the large encapsulated AuNPs, the apparent activation energies (Ea) of both composite particles are comparable, implying no obvious correlation with the size of guest AuNPs under the reaction conditions. Investigating the overall physical properties of various composite particles and their catalytic functions, including the reactivity, selectivity, and Ea, can lead to the development of highly practical quasi-homogeneous catalysts in green reaction conditions.